Investigation into the financial problems of School Governing Bodies in Mogoshi Circuit, Capricorn District Limpopo Provice of South Africa - Manamela, K P (University of Limpopo, 2014)
The South African Schools Act (SASA), 1996 (Act No. 84 of 1996) mandates the establishment of School Governing Bodies (SGBs), whose important roles include the management of school funds. This role includes planning, reviewing, controlling and approving the school budget in accordance with the school's needs. The SGB is ultimately required to account to the Department of Education (DoE), parents and the community for the public funds they manage. However, schools fail to execute this legal mandate effectively and efficiently. Both quantitative and qualitative research methods were employed to complement each other in an attempt to investigate the problems experienced by school governing bodies in executing their financial management functions. Questionnaires, focus group interviews and document reviews were used to gather data. It emerged from the findings of the study that school governors in Mogoshi Circuit are also facing serious financial management problems. Financial management and financial accountability - the sine qua none of effective and efficient management of school finances, pose a challenge. The study found, for example, that the majority of governors in rural areas are elderly people, who are mostly either illiterate or semi-illiterate and lack the capacity to execute their governance roles efficiently and effectively. A once-off or hit and run unaccredited training, which is often provided to the elected SGB members, is relatively not helpful. This inhibits financial accountability. To this end, the study proposed substantial recommendations, which, if implemented, could bring a resolve to the problems and challenges posed.
Thesis (MPA.) -- University of Limpopo, 2014
Keywords: School governing bodies; School finances; 371.20700968; Education -- South Africa -- Finance; School management and organization -- South Africa -- Limpopo; School management teams; School boards members -- South Africa -- Limpopo